Process of defining institutional priorities for research in the Peruvian Social Health Insurance, 2020-2022 - Tenorio-Mucha, Janeth (2020)
Introduction: Health research priorities definition address research efforts to the promotion of health science, technology, and innovation. Material and Methods: Health research priorities in the Peruvian Social Security for the period 2020-2022 was carried out in four stages using a systematic, structured, participatory and sequential process. Results: First, the progress of the research in the priorities of the period 2017-2019 was evaluated. In the second stage, various sources were consulted to identify disease-oriented research needs and the framework for priorities oriented to health systems and health interventions. The third stage consisted of an expanded consultation to select priority disease-oriented topics. Finally, a participatory and multidisciplinary workshop was developed to select themes, subtopics, and priority areas for research. Conclusion: The final product was the definition of 11 priority themes, seven for diseases and four for health systems and health interventions.